A kind of carbon-containing silicon dioxide hollow sphere and preparation method thereof
By adding polyacrylic acid and aqueous ammonia solution in the process of preparing the hollow silica spheres and using a specific silicon source for heat treatment, the problem of insufficient thermal stability of the carbon-containing silica hollow spheres in the prior art is solved, and carbon-containing silica hollow spheres with good spherical shape, monodispersity and controllable particle size are prepared.
Patent Information
- Application Number
- CN202211088942.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to prepare carbon-containing silica hollow spheres with high temperature resistance, good spherical shape and monodispersity, controllable particle size and carbon content, and the existing materials lack thermal stability at high temperatures.
By mixing the aqueous solution containing polyacrylic acid and the aqueous ammonia solution to form an emulsion white emulsion, then adding a mixed silicon source composed of γ-aminopropyltriethoxysilane and ethyl orthosilicate, and then preparing a hollow sphere of carbon dioxide after centrifugation and heat treatment.
The prepared carbon-containing silica hollow spheres have good spherical shape and monodispersity, controllable particle size, uniform distribution of carbon elements, and can maintain structural stability at high temperatures. They are suitable for drug carriers or catalyst carriers.
Smart Images

Figure CN116282047B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a carbon-containing silicon dioxide hollow sphere and a preparation method thereof. Background Art
[0002] Hollow spherical nanostructured materials have a shell thickness of nanometer scale and a huge internal space. Compared with solid nanospheres of the same size, they have the characteristics of low density, large specific surface area and high stability. They are widely used in catalysts, semiconductors, magnetic materials and other fields, and have broad application prospects in separation, adsorption, catalysis, drug sustained release and other aspects.
[0003] In recent years, silica nanomaterials have become a research hotspot due to their good chemical stability, non-toxicity, and easy functionalization of surface hydroxyl groups. Researchers have conducted extensive research on how to prepare silica nanomaterials with special structures. Carbonaceous materials are electrically lossy absorbing materials. By controlling the carbon content in the composite material, the dielectric properties of the material can be regulated. At present, the main method for preparing hollow silica nanospheres is the template method, which can be divided into soft template method and hard template method according to the existence form of the template. The hard template method mainly uses nanoparticles or latex particles as templates, and then uses high-temperature calcination or etching to remove the template. The soft template method uses micelles, vesicles, bubbles, etc. as templates to synthesize hollow silica spheres. The patent with publication number CN100494057 discloses a method for preparing hollow silica spheres. The method for preparing hollow silica spheres of the present invention is characterized in that an alcohol solvent is added to an ammonia solution containing 3-500 g / L of polyelectrolyte to form a colloidal solution, and then 1.1-4.4 mol / L of silicon source precursor is added dropwise at a rate of 0.05-0.2 ml / hour according to a volume ratio of silicon source precursor to ammonia water of 1:15-2:1, and the reaction is carried out at 10-40°C in a closed container for 2-24 hours, and then the product is washed and dried; the concentration of the ammonia water is 10-25% in terms of ammonia mass percentage, and the volume ratio of the alcohol solvent to the ammonia water is 3:1-25:1. The invention is simple to operate, has mild conditions, is pollution-free to the environment, has a high yield, and is suitable for mass production; the obtained hollow silica spheres are loose in texture, have an inner diameter of 10-250 nanometers, and a wall thickness of 10-40 nanometers, can be adjusted by changing the concentration of the polyelectrolyte solution or the volume ratio of the silicon source precursor to ammonia water, and can be used as drug carriers or catalyst carriers; the hollow sphere shell component prepared by the method is pure silica material and does not contain carbon. The patent with publication number CN106110329A discloses a method for preparing organic-inorganic composite hollow silica nanospheres. The preparation method comprises the following steps: mixing tetraethoxysilane and organic sulfide in a preset ratio, adding an alkaline suspension of sodium polyacrylate nanosphere aggregates prepared with ethanol as solvent, stirring at a preset temperature to obtain a composite precipitate, and then centrifugally washing and drying to obtain an organic-inorganic composite hollow silica nanosphere, which can be used for drug delivery. The hollow silica shell material prepared by the method is a composite of an organic sulfide group and silica. The sulfur content in the shell layer can be regulated by changing the silicon source ratio, but the regulation and research of the carbon element in the hollow sphere shell layer component is not involved. In addition, the existing literature does not study the thermal stability of hollow spheres, and cannot provide heat-resistant carbon-containing hollow silica sphere materials. Summary of the invention
[0004] Purpose of the invention: In view of the deficiencies of the prior art, the present invention aims to provide a carbon-containing hollow silica sphere which is resistant to high temperatures, has good sphericity and monodispersity, and has controllable particle size and carbon content. In addition, the present invention also provides a method for preparing the carbon-containing hollow silica sphere.
[0005] Technical solution: The carbon-containing silicon dioxide hollow sphere of the present invention has a shell made of an amorphous material composed of three elements: Si, O and C, wherein the C element accounts for 5.6%-34.7% of the O element, and the C element mainly exists in the form of CC, and the remaining part exists in the form of OC-Si, CO, C=O and OC=O;
[0006] Furthermore, the outer diameter of the hollow sphere is 80-300 nm, and the wall thickness is 30-60 nm.
[0007] The method for preparing the carbon-containing hollow silicon dioxide spheres of the present invention comprises the following steps:
[0008] (1) adding an aqueous solution containing polyacrylic acid to an aqueous ammonia solution and mixing them thoroughly to completely dissolve the polyacrylic acid in the aqueous ammonia solution to obtain a uniform and transparent mixed solution;
[0009] (2) adding the mixed solution into an ethanol solvent under stirring to obtain a milky white emulsion;
[0010] (3) dropping a mixed silicon source consisting of γ-aminopropyltriethoxysilane and ethyl orthosilicate into the milky white emulsion, mixing thoroughly, and then centrifugally drying to obtain a product;
[0011] (4) The product is first subjected to heat treatment in a muffle furnace, the temperature is raised from room temperature to 600-800°C, and then subjected to heat preservation treatment, thereby obtaining carbon-containing silicon dioxide hollow spheres.
[0012] Furthermore, in step (1), the mass fraction of polyacrylic acid is 40-60%, preferably 50%, the average molecular weight of polyacrylic acid is 2000-4000, preferably 3000, the mass fraction of ammonia in the ammonia solution is 25-28%, preferably 25%, and the mass ratio of the polyacrylic acid solution to the ammonia solution is (1:22)-(50:91), preferably 3.5-7:100.
[0013] Furthermore, in step (2), the amount of ethanol used is 11-35 times, preferably 17.5 times, the amount of ammonia water used.
[0014] Furthermore, in step (3), the mass ratio of γ-aminopropyltriethoxysilane to ethyl orthosilicate is ≤1:4, preferably 1:4, the mass ratio of the mixed silicon source to polyacrylic acid is (1:1)-(4:1), preferably (2:1)-(4:1), the mixed silicon source and the milky white emulsion are stirred and mixed in a water bath, the mixing temperature is 20-80°C, the mixing time is 2-10h, the stirring speed is 500-600rpm, the centrifugal treatment conditions are: the centrifugal speed is 8000-12000rpm, the centrifugal time is 2-8min, and the drying treatment conditions are: the drying temperature is 70-90°C, and the drying time is 10-14h.
[0015] Furthermore, in step (4), the heating rate is 4-6°C / min, preferably 5°C / min, and the insulation time is 1-3h, preferably 2h.
[0016] Principle of the invention: The carbon-containing silicon dioxide hollow sphere material prepared by the present invention can regulate the sphericity, surface smoothness and dispersibility of the hollow sphere by adjusting the silicon source ratio; the main source of carbon elements in the hollow spheres is polyacrylic acid, and the purpose of regulating the carbon content in the material can be achieved by changing the heat treatment temperature. As the temperature increases, the relative ratio of the overall carbon element to the oxygen element shows a downward trend. The hollow spheres with small particle size have higher structural stability under the same heat treatment conditions, that is, they can maintain the shape of the hollow spheres without breaking.
[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0018] (1) The carbon-containing hollow silica spheres prepared by the present invention have carbon elements evenly distributed in the shell layer of the hollow silica-based spheres, which can have the performance advantages of both the silica matrix and carbon;
[0019] (2) The carbon content of the carbon-containing hollow silicon dioxide spheres prepared by the present invention can be effectively controlled by the heat treatment temperature;
[0020] (3) The preparation method adopted by the present invention has a simple process, and the obtained hollow spheres have good sphericity and monodispersity, and the particle size is controllable and the structural stability under heat treatment conditions can be improved by adjusting the particle size. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The SEM morphology images of the carbon-containing silicon dioxide hollow spheres prepared in Examples 1-3 and Comparative Example 6 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Comparative Example 6;
[0022] Figure 2The XPS full spectrum of the carbon-containing silicon dioxide hollow spheres prepared in Example 1 of the present invention and the peak spectra of silicon, oxygen and carbon elements respectively;
[0023] Figure 3 This is a TEM morphology image of the carbon-containing silicon dioxide hollow spheres not subjected to heat treatment obtained in Example 1 of the present invention;
[0024] Figure 4 The XRD pattern of the carbon-containing silicon dioxide hollow spheres without heat treatment prepared in Example 1 of the present invention;
[0025] Figure 5 This is a particle size distribution diagram of the carbon-containing silicon dioxide hollow spheres without heat treatment prepared in Example 1 of the present invention;
[0026] Figure 6 This is a wall thickness measurement diagram of the carbon-containing silicon dioxide hollow spheres without heat treatment prepared in Example 1 of the present invention;
[0027] Figure 7 The SEM morphology images of the carbon-containing silicon dioxide hollow spheres prepared in Examples 1 and 4 of the present invention, (a) is Example 1, and (b) is Example 4;
[0028] Figure 8 This is a particle size distribution diagram of the carbon-containing silicon dioxide hollow spheres without heat treatment prepared in Example 4 of the present invention;
[0029] Fig. 9 These are SEM morphology images of carbon-containing silicon dioxide composite materials obtained without heat treatment in Example 1 and Comparative Examples 1-5 of the present invention, wherein (b) is Example 1, (a) is Comparative Example 1, (c) is Comparative Example 2, (d) is Comparative Example 3, (e) is Comparative Example 4, and (f) is Comparative Example 5. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with embodiments and drawings.
[0031] Example 1: The carbon-containing silicon dioxide hollow sphere of the present invention has a shell made of an amorphous material composed of three elements: Si, O and C, with an outer diameter of 80-300 nm and a wall thickness of 30-60 nm.
[0032] The preparation steps of the above-mentioned hollow silicon dioxide spheres containing carbon are as follows: 0.5 g of an aqueous solution containing 50% polyacrylic acid (average molecular weight of 3000) is added to 4 mL of an aqueous ammonia solution (NH3 content of 25%), and ultrasonically mixed for 30 minutes to obtain a uniform and transparent mixed solution; 70 mL of ethanol solvent is added to the mixed solution under stirring at a speed of 550 rpm to obtain a milky white emulsion; 1 g of a mixed silica solution consisting of γ-aminopropyltriethoxysilane and ethyl orthosilicate in a mass ratio of 1:4 is added to the mixture; After uniform ultrasonic mixing at a source, the mixture was dripped into the milky white emulsion. After magnetic stirring at room temperature for 6 hours, the mixture was centrifuged at 10000 rpm for 10 minutes to separate the product. The product obtained by centrifugation was placed in a blower dryer and dried at 80°C for 12 hours to obtain the product (at this time, the C element:O element in the product is 23:77). The product was placed in a muffle furnace for heat treatment from room temperature to 600°C at a heating rate of 5°C / min, and then kept warm for 2 hours to obtain carbon-containing silica hollow spheres.
[0033] Example 2: The difference from Example 1 is that in the preparation method, the product is placed in a muffle furnace for heat treatment first, the temperature is increased from room temperature to 700°C at a heating rate of 5°C / min, and then kept warm for 2h to obtain carbon-containing silicon dioxide hollow spheres.
[0034] Example 3: The difference from Example 1 is that in the preparation method, the product is placed in a muffle furnace for heat treatment first, the temperature is increased from room temperature to 800°C at a heating rate of 5°C / min, and then kept warm for 2h to obtain carbon-containing silicon dioxide hollow spheres.
[0035] Example 4: The difference from Example 1 is that in the preparation method, the amount of the aqueous solution containing 50% polyacrylic acid (average molecular weight is 3000) is 0.25 g, and the mass ratio of polyacrylic acid to ammonia is 7:100.
[0036] Comparative Example 1: The difference from Example 1 is that, in the preparation method, the silicon source only includes tetraethyl orthosilicate, and no heat treatment is included.
[0037] Comparative Example 2: The difference from Example 1 is that in the preparation method, the mass ratio of γ-aminopropyltriethoxysilane to ethyl orthosilicate in the mixed silicon source is 2:3, and heat treatment is not included.
[0038] Comparative Example 3: The difference from Example 1 is that in the preparation method, the mass ratio of γ-aminopropyltriethoxysilane to ethyl orthosilicate in the mixed silicon source is 3:2, and heat treatment is not included.
[0039] Comparative Example 4: The difference from Example 1 is that in the preparation method, the mass ratio of γ-aminopropyltriethoxysilane to ethyl orthosilicate in the mixed silicon source is 4:1, and heat treatment is not included.
[0040] Comparative Example 5: The difference from Example 1 is that, in the preparation method, the silicon source only includes γ-aminopropyltriethoxysilane, and no heat treatment is included.
[0041] Comparative Example 6: The difference from Example 1 is that, in the preparation method, the product is placed in a muffle furnace for heat treatment first, the temperature is increased from room temperature to 900°C at a heating rate of 5°C / min, and then kept warm for 2h to obtain carbon-containing silicon dioxide hollow spheres.
[0042] Microscopic morphology characterization tests were performed on the carbon-containing carbon dioxide composite materials prepared in Example 1 to Example 4 and Comparative Example 1 to Comparative Example 6.
[0043] Depend on Figure 1 As shown in the figure, when the heat treatment temperature is 600℃, the prepared hollow spheres begin to break, and the spherical shell fragments are scattered around the hollow spheres; when the temperature rises to 700℃ and 800℃, the proportion of broken spheres increases; and when the temperature reaches 900℃, the hollow spheres are basically all broken, and there are no complete hollow spheres. Figure 2 As shown, the hollow spheres after heat treatment contain three elements: Si, C, and O. Among them, the Si element exists in the form of SiO4, SiO3C, and SiO2C2; the O element exists in the form of O-Si and OC; the C element mainly exists in the form of CC, and part of it forms OC-Si, CO, C=O, and OC=O.
[0044] Depend on Figures 3 to 6 It can be seen that the product obtained in Example 1 without heat treatment has an obvious hollow sphere structure and is amorphous. The particle size of the spheres is mainly distributed between 150-300 nm, and the average wall thickness is 33.8 nm.
[0045] Depend on Figure 7 It can be seen that the particle size distribution of the sample prepared with 0.5g polyacrylic acid is wider, the hollow spheres with large particle size are broken after calcination, while the hollow spheres with small particle size can maintain the integrity of the structure; while the particle size of the sample prepared with 0.25g polyacrylic acid is relatively small, and the complete hollow sphere morphology is basically maintained after heat treatment. Figure 8 It can be seen that the particle size of the spheres obtained in Example 4 without heat treatment is mainly distributed in the range of 80-140 nm.
[0046] Depend on Fig. 9As shown, when γ-aminopropyltriethoxysilane is not added to comparative example 1 and pure ethyl orthosilicate is used, the surface of the obtained hollow sphere is rough and the sphericity is not high. The shell of the hollow sphere is composed of silicon dioxide particles with a diameter of about 30 nm, and the hollow spheres are severely agglomerated and have poor dispersibility. When the mass ratio of γ-aminopropyltriethoxysilane to ethyl orthosilicate in the mixed silicon source in Example 1 is 1:4, hollow spheres with smooth surface, excellent sphericity and good dispersibility are obtained. When the mass ratio of γ-aminopropyltriethoxysilane to ethyl orthosilicate in the mixed silicon source in comparative example 2 is 2:3, the formation of hollow spheres is not observed, but solid particles with smaller particle size are obtained. As the relative proportion of γ-aminopropyltriethoxysilane in comparative examples 3 to 4 continues to increase, the spherical particles disappear, and a dense bulk material is obtained.
[0047] The dielectric properties of the materials prepared in Example 1 and Comparative Example 6 were calculated to verify that different C contents at different heat treatment temperatures can regulate the dielectric properties of the obtained materials. During the calculation process, the spherical shell material is assumed to be composed of two materials: amorphous carbon and silicon dioxide. Among them, in the range of 2-18GHz, the real part of the complex dielectric constant of amorphous carbon varies between 180-38, and the imaginary part varies between 130-40. In the calculation, the real part of amorphous carbon is taken as 109, and the imaginary part is taken as 85 (Jie Shuai. Study on the electromagnetic wave absorption performance of gypsum board and mineral wool board with carbon black as absorbent [D]. Hebei University of Technology, 2015.), and the density of amorphous carbon is taken as 1.9g / cm 3 In the calculation process, the real part of the complex dielectric constant of silicon dioxide is taken as 3.9, the imaginary part is taken as 0.00117 (Yang Juan, Du Yongguo, Zhang Weijun, et al. Research Progress of Low Temperature Co-fired Substrate Materials [J]. Materials Guide, 2006, 20(10):5.), and the density of silicon dioxide is taken as 2.50 g / cm 3 . In Example 1, the atomic ratio of C to O is 5.60%, and the mass ratio of amorphous C to SiO2 is 11.20%, which is converted into a volume ratio of amorphous C to SiO2 of 2.95%, and the volume fraction of amorphous C in the shell is 2.86%. In Comparative Example 6, the atomic ratio of C to O is 34.7%, and the mass ratio of amorphous C to SiO2 is 69.4%, which is converted into a volume ratio of amorphous C to SiO2 of 18.26%, and the volume fraction of amorphous C in the shell is 15.44%. The dielectric properties of the shell are calculated according to the Rayleigh Mixing formula (Shivola, AHSelf-consistency aspects of dielectric mixing theories[J]. Geoscience & Remote Sensing IEEE Transactions on, 1989.):
[0048]
[0049] where ε eff is the dielectric constant of the composite material, i.e., the shell; ε0 is the dielectric constant of the matrix phase, i.e., the dielectric constant of SiO2; ε1 is the dielectric constant of the filling phase, i.e., the dielectric constant of amorphous C; f1 is the volume fraction of the filling phase, i.e., the volume fraction of amorphous C in the shell. Substituting the parameters into the above formula and solving it, we can obtain that in Example 1, the volume fraction of C is 2.86%, the real part value of the complex dielectric constant of the shell is 4.22, the imaginary part value is 0.0182, and the electric loss tangent value is 4.31×10 -3 In comparative example 6, the volume fraction of C is 15.44%, the real part of the complex dielectric constant of the shell is 5.87, the imaginary part is 0.1202, and the electric loss tangent is 2.05×10 -2 . It can be seen from the calculation results that with the increase of heat treatment temperature, the volume fraction of amorphous C increases, and the real part value, imaginary part value and electric loss tangent value of the complex dielectric constant of the shell material all increase, thereby realizing the regulation of the dielectric properties of the shell layer. The samples prepared in Example 1 and Comparative Example 6 are composite materials composed of shell materials and internal air phase. According to Lichtenecker's logarithmic mixing rule, the dielectric properties of the composite materials in the composite material system will change with the proportion of each component, as shown in the following formula (Chen YC, Lin HC, Lee Y D. The Effects of Filler Content and Size on the Properties of PTFE / SiO2 Composites [J]. Journal of Polymer Research, 2003, 10 (4): 247-258.):
[0050]
[0051]
[0052] Where ε' is the dielectric constant of the composite material, and are the volume fractions of phase 1 and phase 2, ε'1 and ε'2 are the dielectric constants of phase 1 and phase 2, tanδ is the dielectric loss tangent of the composite material, and tanδ1 and tanδ2 are the dielectric loss tangent of phase 1 and phase 2. It can be seen from the above formula that under the same other conditions, the dielectric properties of the shell material will directly affect the dielectric properties of the overall material, so the dielectric properties of the obtained material can be regulated by different C contents at different heat treatment temperatures.
Claims
1. A carbon-containing silicon dioxide hollow sphere, characterized in that: The shell of the hollow sphere is an amorphous material composed of three elements: Si, O and C, wherein the atomic ratio of C to O is 5.6%-34.7%. The preparation method of the carbon-containing silicon dioxide hollow sphere is as follows: (1) adding an aqueous solution containing polyacrylic acid into an aqueous ammonia solution and mixing them thoroughly to obtain a uniform and transparent mixed solution; (2) adding the mixed solution into the stirring ethanol solvent to obtain a milky white emulsion; (3) dropping a mixed silicon source consisting of γ-aminopropyltriethoxysilane and ethyl orthosilicate into the milky white emulsion, mixing thoroughly, and then centrifugally drying to obtain a product; (4) The product is first subjected to heat treatment in a muffle furnace, the temperature is raised from room temperature to 600-800°C, and then subjected to heat preservation treatment, so as to obtain carbon-containing hollow silica spheres; in step (1), the mass fraction of the polyacrylic acid is 40-60%, and the average molecular weight of the polyacrylic acid is 2000-4000; in step (3), the mass ratio of the γ-aminopropyltriethoxysilane to ethyl orthosilicate is 1:4, and the mass ratio of the mixed silicon source to the polyacrylic acid is (1:1)-(4:1).
2. The carbon-containing silicon dioxide hollow sphere according to claim 1, characterized in that: The outer diameter of the hollow sphere is 80-300nm, and the wall thickness is 30-60nm.
3. A method for preparing carbon-containing hollow silicon dioxide spheres according to claim 1, characterized in that: Follow these steps: (1) adding an aqueous solution containing polyacrylic acid into an aqueous ammonia solution and mixing them thoroughly to obtain a uniform and transparent mixed solution; (2) adding the mixed solution into the stirring ethanol solvent to obtain a milky white emulsion; (3) dropping a mixed silicon source consisting of γ-aminopropyltriethoxysilane and ethyl orthosilicate into the milky white emulsion, mixing thoroughly, and then centrifugally drying to obtain a product; (4) The product is first heat-treated in a muffle furnace, the temperature is raised from room temperature to 600-800°C, and then heat-insulated to obtain carbon-containing silicon dioxide hollow spheres.
4. The preparation method according to claim 3, characterized in that: In step (1), the mass fraction of ammonia in the ammonia solution is 25-28%.
5. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the aqueous solution of polyacrylic acid to the aqueous ammonia solution is (1:22)-(50:91).
6. The preparation method according to claim 3, characterized in that: In step (2), the volume amount of ethanol is 11-35 times the volume amount of the ammonia solution.
7. The preparation method according to claim 3, characterized in that: In step (3), the mixing temperature is 20-80°C and the mixing time is 2-10 hours.
8. The preparation method according to claim 3, characterized in that: In step (3), the centrifugal conditions are: centrifugal speed is 8000-12000rpm, and the centrifugal time is 2-8min.
9. The preparation method according to claim 3, characterized in that: In step (4), the heating rate is 4-6°C / min.
Citation Information
Patent Citations
Organic-inorganic composite silicon dioxide nano hollow spheres and preparing method
CN106110329A
KR20200068148A